The impact of medical tourism on the quality of organizational and functional changes in the Polish healthcare system - Marcin Olkiewicz (UTMS Journal of Economics, 2016)
The role of Medical Tourism in the process of a complex satisfaction of the prosumers and the impact played in the organizational and functional changes in the Polish healthcare system. The analysis of the literature on the subject as well as an analysis of the documentation were the inspiration to write this work. The main emphasis was put on stating the conditions stimulating the development of this sector of the economy as well as the risk factors determining the quality of process changes in the healthcare system (functioning of public hospitals). To approximate the characteristics of the involved risk within the framework of health tourism functioning in the conditions of a market economy. Selected research methods allowed to present the motives behind undertaken actions of both the regulators as well as participants of the health tourism. Polish accession to the EU was an important impulse changing the way of thinking about health tourism in healthcare as well as, what is important, changes in the institutional and financial policy in Poland. In order to meet health-oriented demands of a prosumer, there should be a coordinated and effective informational system, aimed at improving the quality, reliability, availability of information concerning health tourism.
Keywords: M19; L8; I11; I15; 330; health tourism; health services; quality